Prevention of upper gastrointestinal bleeding in critically ill Chinese patients: a randomized, double-blind study evaluating esomeprazole and cimetidine. (3rd August 2018) - Lou, Wenhui; Xia, Ying; Xiang, Peng; Zhang, Liangqing; Yu, Xiangyou; Lim, Sam; Xu, Mo; Zhao, Lina; Rydholm, Hans; Traxler, Barry; Qin, Xinyu
Abstract: Objective: To assess the efficacy and safety of esomeprazole in preventing upper gastrointestinal (GI) bleeding in critically ill Chinese patients, using cimetidine as an active comparator. Methods: A pre-specified non-inferiority limit (5%) was used to compare rates of significant upper GI bleeding in this randomized, double-blind, parallel-group, phase 3 study across 27 intensive care units in China. Secondary endpoints included safety and tolerability measures. Patients required mechanical ventilation and had at least one additional risk factor for stress ulcer bleeding. Patients were randomized to receive either active esomeprazole 40 mg, as a 30-min intravenous (IV) infusion twice daily, and an IV placebo cimetidine infusion or active cimetidine 50 mg/h, as a continuous infusion following an initial bolus of 300 mg, and placebo esomeprazole injections, given up to 14 days. Patients were blinded using this double-dummy technique. Results: Of 274 patients, 2.7% with esomeprazole and 4.6% with cimetidine had significant upper GI bleeding (bright red blood in the gastric tube not clearing after lavage or persistent Gastroccult-positive "coffee grounds" material). Non-inferiority of esomeprazole to cimetidine was demonstrated. The safety profiles of both drugs were similar and as expected in critically ill patients. Conclusions: Esomeprazole is effective in preventing upper GI bleeding in critically ill Chinese patients, as demonstrated by the non-inferiority analysis using cimetidine as an active control. Trial registration: ClinicalTrials.gov identifier NCT02157376.